Dopa-responsive dystonia (DRD): systematic search in Latin America - Zelada-Ríos, Laura (2022)
Dopa-responsive dystonia (DRD) encompasses a heterogenous group of primary dystonias, caused by enzymatic deficiencies across the amines pathway and, by definition, show as their main characteristic a favorable and sustained response to levodopa. There are up to 6 genes associated with DRD, including pathogenic variants of the GCH1 gene as the most frequently involved. The typical presentation of DRD is characterized by start in childhood, lower limb-onset dystonia with daytime fluctuation, mild parkinsonism, and a sustained response to low doses of levodopa. A systematic literature search on DRD reported cases in Latin America is presented.